Prevalence rates of post-traumatic stress disorder in prisoners - Baranyi, G; Cassidy, M; Fazel, S; Priebe, S; Mundt, A (Oxford University Press, 2018)
Exposure to violence and traumatic experiences are frequent in people with criminal justice involvement. Although this may lead to post-traumatic stress disorder (PTSD), no review has synthetized findings in this setting. We conducted a systematic review and meta-analysis to estimate prevalence rates of PTSD in prison populations. Original studies reporting prevalence rates of PTSD in unselected samples of incarcerated people were systematically searched between 1980 and June 2017. Data were pooled using random effects meta-analysis and sources of heterogeneity for pre-specified characteristics were assessed by meta-regression. Fifty-six samples including 21,099 imprisoned men and women from 20 different countries were identified. Point prevalence rates of PTSD ranged from 0.1% to 27% for male, and from 11% to 38% for female prisoner populations. Random effects pooled point prevalence rates were 6.2% (95% CI: 3.9, 9.0) in male and 21.1% (95% CI: 16.9, 25.6) in female prisoners. The heterogeneity between the included studies was very high. Higher prevalences were reported in female samples, smaller study sizes (n < 100), and for investigations based in high-income countries. Existing evidence shows high levels of PTSD among imprisoned people, especially women. Psychosocial interventions to prevent violence, especially against children and women, and to mitigate its consequences in marginalized communities need to be improved. Trauma-informed approaches for correctional programs and scalable PTSD treatments in prisons require further consideration.